Phraseologisms Related to Food in English as a Reflection of Popular Thought (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Using the example of phraseological units of the Andean language with the component'gastronomic product', the article shows that in the English-speaking environment the most importantare the values of the material, physical and social level, while emotional, spiritual and moral valuesare poorly represented. Using the analysis of the expression plan of phraseological units, such an areaof Andean life as taste habits (in relation to nutrition: food and drinks) is described.